Surgical Decompression in the Treatment of Diabetic Peripheral Neuropathy: A Systematic Review and Meta-analysis - Tu, Yiji; Lineaweaver, William Charles; Chen, Zenggan; Hu, Junda; Mullins, Fred; Zhang, Feng (Journal of Reconstructive Microsurgery, 2017)
Background Over the last decade, surgical decompression procedures have been commonly used in the treatment of diabetic peripheral neuropathy. However, the effectiveness of them remains to be proved.Methods A comprehensive literature search of databases including PubMed-Medline, Ovid-EMBASE, and Cochrane Library was performed to collect the related literatures. The Medical Subject Headings used were “diabetic neuropathy,” “surgical decompression,” and “outcomes.” The methodological index for nonrandomized studies was adopted for assessing the studies included in this review. Analyses were performed with Review Manager (Version 5.3, Copenhagen: The Nordic Cochrane Centre, the Cochrane Collaboration, 2014).Results A total of 12 literatures (including 8 prospective and 4 retrospective) encompassing 1,825 patients with DPN were included in the final analysis. Only one literature was identified as a randomized controlled trial. The remaining 11 literatures were observational studies; 7 of them were classified as upper-extremity nerve decompression group and 4 of them were classified as lower-extremity nerve decompression group. Meta-analysis shows that Boston questionnaire symptom severity and functional status of upper extremities, and distal motor latency and sensory conduction velocity of median nerve of DPN patients are significantly improved after carpal tunnel release. Besides, visual analog scale and two-point discrimination are considered clinically and statistically significant in lower extremities after operation.Conclusions The findings from our review have shown the efficacy of surgical decompression procedures in relieving the neurologic symptoms and restoring the sensory deficits in DPN patients. As there are few high-quality randomized controlled trials or well-designed prospective studies, more data are needed to elucidate the role of surgical procedures for DPN treatment in the future.
Keywords: diabetes; peripheral neuropathy; nerve decompression